Association between metabolic score for visceral fat index and BMI-adjusted skeletal muscle mass index in American adults - Yifan Zhou; Xiangjie Su; Haitao Tan; Jun Xiao (Lipids in Health and Disease)
Abstract Background The metabolic score for visceral fat (METS-VF) is a recently identified index for evaluating visceral fat, also referred to as abdominal obesity. The skeletal muscle mass index (SMI) serves as a critical measure for assessing muscle mass and sarcopenia. Both obesity and the reduction of muscle mass can significantly affect human health. However, research exploring the relationship between METS-VF and SMI remains limited. This study aims to investigate whether a association exists between these two indices, and if so, to elucidate the nature of their interactions. Methods We conducted a cross-sectional study using data from the NHANES database, focusing on U.S. adults aged 20 years and older from 2013 to 2018. Controlling for relevant covariables, we primarily investigated the association between METS-VF and SMI values utilizing weighted multivariable linear regression models. Additionally, we assessed the diagnostic efficacy of METS-VF for sarcopenia. Results A total of 3,594 participants were included in this study for analysis. The final adjusted model from the weighted multivariable linear regression indicated that METS-VF was negatively associated with SMI, with a coefficient of β = -0.13 (95% CI: -0.14, -0.12; P < 0.001). Subgroup analyses further demonstrated that this negative association was consistent across different populations. Notably, the negative association varied significantly between diabetic and nondiabetic population, as well as among populations classified by different BMI categories. Additionally, threshold effect analysis identified a significant inflection knot at 6.33. The characteristic curves of the subjects’ work illustrated that, compared to other indicators, METS-VF exhibited excellent diagnostic efficacy for sarcopenia, with an area under the curve (AUC) of 0.825. Conclusion Our results indicate that METS-VF is negatively correlated with SMI among adults in the United States, suggesting that visceral obesity exerts a detrimental effect on muscle mass. Furthermore, METS-VF shows potential as a valuable indicator for assessing SMI and sarcopenia. These findings underscore the importance of considering lipid metabolism disorders in the context of muscle health and highlight the potential for developing prevention strategies for sarcopenia.